THE EFFECT OF REPLACEMENT OF COMMERCIAL RATIO WITH NON-COMMERCIAL RATIO ON LAYER PRODUCTIVITY ISA BROWN - V. T., Fikgiannisa; Wibawa, A. A. P. P.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2023)
This study aims to determine how the effect of partial replacement of commercial rations with non-commercial rations on the productivity of laying hens isa brown. The design used in this study was a completely randomized design (CRD) with 4 treatments and 4 replications using 10 chickens in each replication. The four treatments were P0: chickens were given a commercial ration PL241, P1: chickens were given non commercial rations (composition 1), P2: chickens were given non-commercial rations (composition 2), and P3: chickens were given non-commercial rations (composition 3). The results showed that the effect of partial replacement of commercial rations with non-commercial rations on the productivity of laying hens was a brown got the same results on feed consumption in all treatments, in treatment P1 the results of Hen Day Production (HDP), total egg weight, average egg weight, and the same ration conversion as the P0 treatment. Then in treatment P2 and P3 the results of Hen Day Production (HDP), total egg weight, and average egg weight were lower than P0 treatment, while the ration conversion got higher results than P0 treatment. based on the results of the study it can be concluded that non-commercial ration 1 (P1) can be used as an alternative feed seen from the results of the study, namely getting results on ration consumption, Hen Day Production (HDP), total egg weight, and average egg weight, and ration conversion which is the same as the commercial P0 ration, so that by partially replacing the commercial ration with a non-commercial ration on the productivity of laying hens isa brown, the P1 non-commercial ration treatment is very suitable for use. Keywords: Isa Brown Laying Hens, Non-Commercial, Productivity.